O uso do TikTok pela geração Z: um olhar a partir da perspectiva de McLuhan - Duda, Pedro da Silva (2025)
Information and Communication Technologies (ICTs) in virtual social media have emerged as dynamic and influential mechanisms in reshaping communication practices and information consumption, particularly among Generation Z, notable for their innate familiarity with digital technologies. The rise of virtual social media platforms coincided with the emergence of this generation, amplifying their everyday impact. Within this context, this study aims to understand how TikTok influences Gen Z users’ content consumption practices. The transformations stemming from TikTok’s use prompt a critical reflection on ICTs’ role not merely as information transmitters but as active agents shaping perceptions and behaviors. The analysis is grounded in Marshall McLuhan’s theory “The Medium is the Message,” which examines how TikTok’s inherent characteristics, such as short-form videos and sensory hyperstimulation, condition communication that happens through the platform and shape people’s behavior. Methodologically, a descriptive qualitative approach was adopted, using semi-structured interviews and content analysis for data interpretation.